Clay Science and Technology 2021
DOI: 10.5772/intechopen.92408
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Clay in Pharmaceuticals

Abstract: Clay has its widespread applications in pharmaceuticals from ancient world to modern era. It is one of the excellent excipients present in the commercially available pharmaceuticals. Its use in many of dosage forms viz. in suspension, emulsion, ointments, gels, tablet and as drug delivery carrier as suspending agent, emulsifying agent, stiffening agent, binder, diluent, opacifier, and as release retardant have been explored in many studies. Variety of minerals is used as both excipient and as an active ingredi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Clay minerals are often used in the pharmaceutical industry, either as net or activated ingredients. The complex of chemical-physical characteristics of clay nanomaterials makes these nanostructures suitable for use in the controlled loading and release of different classes of therapeutic agents, including anticancer drugs [ 43 ]. Clay minerals are able to interact with the molecules of different therapeutic agents, but they can also interact with the different additive constituents (such as polymers) that can be used in the production of nano-formulated medicines with optimal properties [ 44 ].…”
Section: Key Properties Of Nano-clays For Application In the Delivery...mentioning
confidence: 99%
“…Clay minerals are often used in the pharmaceutical industry, either as net or activated ingredients. The complex of chemical-physical characteristics of clay nanomaterials makes these nanostructures suitable for use in the controlled loading and release of different classes of therapeutic agents, including anticancer drugs [ 43 ]. Clay minerals are able to interact with the molecules of different therapeutic agents, but they can also interact with the different additive constituents (such as polymers) that can be used in the production of nano-formulated medicines with optimal properties [ 44 ].…”
Section: Key Properties Of Nano-clays For Application In the Delivery...mentioning
confidence: 99%
“…Udayakumar et al [11] found bentonite useful to increase the temperature bearing capacity and used the bentonite-based composites for naproxen release in a controlled manner. Different analytical techniques found useful for the determination of mechanical-thermal properties of different clay-based composite and nanofibers such techniques are; dynamic mechanical-thermal-analysis (DMTA) (for tensile strength determination) and TGA-DSC analysis [48,49].…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…Cause irritation cannot recommend, some Drugs might demolish due to Enzymatic action, e.g., insulin or penicillin etc., absorption of drugs might be ambiguous, cannot allowed for patient showed insentient and un-supportive behavior, [34] Except oral route use-full for intravenous and intramuscular injections A definite beneficial for an immediate action, useable for insentient, noncooperative patients, and also for diarrhea and vomiting patient May cause pain or sepsis, intravenous injection may react Or cause some kinds of complications, costly, for dosage some aseptic measure and practical skill essentially required [17] Transdermal administration: Surface application, in the form of powder, creams or sprays etc., The transfer of Active ingredients is direct to the targeted area, safe for liver or Gastro-intestinal trac By using this route, a local effect might be observed instead of systematic [68,73] Sprays: direct Inhalation route Direct release of drug to the Lungs Some kinds of delivery devices for spraying the drug are mandatory [68] Implantable administration route Excess drug bioavailability, smallest dosing frequency Requires surgery for drug administration, noxiousness of accompanying chemicals, Cause pain, may cause postoperative effect [49] In the form of Bone Cement Increased Toughness and stiffness…”
Section: Slow Action Mechanism Drugsmentioning
confidence: 99%